POTRET TAMAN PENDIDIKAN AL-QURAN (TPQ) DUSUN PANDA, DESA LEMBANG SANGGAU LEDO, BENGKAYANG - Parwanto, Wendi; Antika, Yuliana; Parayogi, Osman; Wahyuni, Desi (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2024)
Abstract Studies on Al-Qur'an Education (TPQ) in rural areas still need to be carried out, especially in areas that are quite far from the city center, including Panda Hamlet, Bengkayang District, West Kalimantan. This research is a field study which aims firstly to describe the demographic and religious characteristics of Panda hamlet, and secondly to describe the practice of Al-Quran learning at TPQ Darul Ilmi Panda Hamlet, Lembang Village, Sanggau Ledo Sub-district, Bengkayang District, West Kalimantan. Data was collected through observation, interviews and document review. The conclusion of this study is firstly, demographically, the population is diverse in terms of ethnicity and religion but lives in peace and harmony. All residents can carry out religious rituals and practices in peace. Secondly, Al-Quran learning at TPQ Darul Ilmi has been carried out well. Learning uses a combination of traditional and modern methods such as the sorogan method but has been combined with modern models such as the Iqro method. In addition, TPQ Darul Ilmi already has a clear curriculum and effective administration, for example the use of guidebooks which contain reading provisions and restrictions, class levels, attendance list and so on. This creation and innovation is quite appreciative.  Abstrak Studi tentang Taman Pendidikan Al-Qur`an (TPQ) di daerah pedesaan masih perlu dilakukan, terlebih lagi daerah-daerah yang cukup jauh dari pusat kota, termasuk di Dusun Panda, Kabupaten Bengkayang, Kalimantan Barat. Penelitian ini adalah sebuah studi lapangan (field research) yang bertujuan pertama untuk mendeskripsikan karakter demografis dan keagamaan Dusun Panda dan kedua untuk mendeskripsikan praktek Pembelajaran Al-Quran di TPQ Darul Ilmi Dusun Panda, Desa Lembang, Kecamatan Sanggau Ledo, Kabupaten Bengkayang, Kalimantan Barat. Data dikumpulkan melalui observasi, wawancara dan kaji dokumen. Kesimpulan dari studi ini adalah pertama, secara demografis penduduk beragam dari segi suku dan agama namun hidup rukun dan harmonis. Semua penduduk dapat melaksanakan ritual dan praktek keagamaan dengan damai. Kedua, pembelajaran Al-Qur'an di TPQ Darul Ilmi sudah terlaksanana dengan baik. Pembelajaran menggunakan gabungan metode tradisional dan modern seperti metode sorogan namun sudah dikombinasikan dengan model modern seperti metode Iqro. Selain itu, sudah memiliki kurikulum yang jelas dan administrasi yang efektif misalnya menggunakan buku panduan yang berisi ketentuan dan batasan-batasan bacaan, tingkatan kelas, absensi dan sebagainya, kreasi dan inovasi ini cukup apresiatif.